Pengaruh Rasio Likuiditas, Leverage, Rasio Aktivitas, dan Firm Size Terhadap Profitabilitas Pada Perusahaan Sektor Energi yang Terdaftar Bursa Efek Indonesia (BEI) Periode 2018-2022 - Aeraafi, Hasnaning Monica; Hartono, Ulil (Universitas Negeri Surabaya, 2024)
This research analyses the influence of liquidity ratios, leverage, activity ratios and firm size on energy sector companies listed on the Indonesia Stock Exchange for 2018-2022. The type of data used is quantitative data sourced from secondary data. The population in this study are energy sector companies listed on the Indonesian Stock Exchange. The sampling technique used was purposive sampling, and 14 companies were obtained as samples. The data analysis technique uses multiple linear regression. The research results show that the liquidity ratio does not affect profitability, leverage has a negative and significant effect on profitability, the activity ratio has a positive and significant impact on profitability, and firm size has no effect on profitability. Therefore, this research provides recommendations to companies to further increase the activity ratio, which reflects the effectiveness of asset management and pay more attention to leverage movements, which reflect the use of funds originating from debt. Investors can consider leverage and activity ratio before making investment decisions.